Hubungan Antara Self Efficacy dengan Pengambilan Keputusan Karier pada Siswa Kelas XII Putri MA Miftahul Qulub Galis Pamekasan - Nuri Istiqlailia; Ishlakhatus Sa'idah (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2021)
This research was motivated by many students at MA Miftahul Qulub who still lacked confidence in making career decisions. This can be seen from their inability to determine further studies to college as desired. There are also some students who are still confused about what to do after graduation. Self efficacy can influence students in determining the chosen decision making. So that in this study, researchers are interested in conducting research with the title "The Relationship Between Self Efficacy With Career Decision Making in Class XII Female Students of MA Miftahul Qulub Galis Pamekasan". The purpose of this study was to determine whether or not there was a relationship and the magnitude of the relationship between self-efficacy and career decision-making for the class XII female students of MA Miftahul Qulub Galis Pamekasan. This research is a quantitative research with the type of correlational analysis to see the relationship of the two variables of this study. The subjects in this study were 25 people. Data analysis used the Product Moment correlation method with the help of SPSS v.25 software for windows. The results of the correlation analysis showed that the significance value (p) obtained was 0.000, and the correlation coefficient (r) was 0.709. So that in this study the hypothesis is accepted, namely there is a relationship between self-efficacy and career decision making in class XII Putri MA Miftahul Qulub Galis Pamekasan students.